(untitled) (Research, Society and Development, 2021)
Introduction. The epidemic caused by the new Coronavirus - SARS-CoV-2 (COVID 19) affected the world population in many ways, with education being one of the most affected sectors. Professional education is an educational modality that aims to prepare the student for work, and its interruption, besides the educational damages, prevents the insertion in the labor market. Objective. To analyze the knowledge, attitude and perception of professional education students from a health technical school in the countryside of southeastern Brazil regarding the pandemic of COVID-19. Methodology. Cross-sectional descriptive and exploratory study. Students who were enrolled in the first semester of 2020 answered data collected in online forms. Results and Final Considerations. From the total of 396 students, 256 (64.65%) responded to the questionnaire. It is a predominantly young population, most of them aged up to 29 years old, female gender and brown color. In relation to the pandemic, we observed an increase in social and economic vulnerabilities. The students were forced to deal with additional stress factors with the school closing, the social distance and the fear related to the virus and death. Regarding the psychological aspects, most students reported a high level of sadness, anxiety, as well as unwillingness to do daily activities. Information about the pandemic was sought through traditional media, and most students had access to and already used digital media. Despite the study’s limitations, it contributes with important information about the students’ knowledge, attitude, and perception, providing subsidies for planning future actions.